PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN HUTAN RAKYAT DI KABUPATEN KUBU RAYA KALIMANTAN BARAT - Normagiat, Sigit (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2019)
Kubu Raya District Government has created a Forest and Land Rehabilitation program by providing assistance for the development of Hutan Rakyat (HR) on community-owned land. This program aims to enable the recipient community to maintain and even increase the presence of HR in their area. but the success of the program needs to be reviewed from the level of community participation. This study aims to measure the level of community participation in HR management in two sample villages in Kubu Raya District. Using descriptive and inferential methods to analyze the influence of internal and external factors on the level of community participation in HR management. The result is that internal factors consisting of differences in age, sex, education, income, and length of stay did not have a significant influence on community participation in participating in HR management programs. based on the analysis of community participation using the Arnstein criteria, the scores of the two villages were at the level of 4 (four), namely the level of consultation. This means that the community participates based on directions from the relevant agencies, especially when planting in the field. Ideas and inputs from the community are only heard but not necessarily realized in the planning and evaluation stages. The existence of external factors in the form of counseling and market opportunities are considered potential in encouraging community initiatives to participate in HR development programs